Temperature-dependent transformation multiphysics and ambient-adaptive multiphysical metamaterials. (8th November 2021) - Lei, M.; Wang, J.; Dai, G. L.; Tan, P.; Huang, J. P.
Abstract: Temperature-dependent transformation thermotics provides a powerful tool for designing multifunctional, switchable, or intelligent metamaterials in diffusion systems. However, its extension to multiphysics lacks study, in which temperature dependence of intrinsic parameters is ubiquitous. Here, we theoretically establish a temperature-dependent transformation method for controlling multiphysics. Taking thermoelectric transport as a representative case, we analytically prove the form invariance of its temperature-dependent governing equations and definitively formulate the corresponding transformation rules. Finite-element simulations demonstrate solid and robust thermoelectric cloaking, concentrating, and rotating performance in temperature-dependent backgrounds. Two practical applications are further designed with temperature-dependent transformation: one is an ambient-responsive cloak-concentrator thermoelectric device that can switch between cloaking and concentrating; the other is an improved thermoelectric cloak with nearly thermostat performance inside. Our theoretical frameworks and application design may provide guidance for efficiently controlling temperature-related multiphysics and enlighten subsequent intelligent multiphysical metamaterial research.